MASS MEDIA CHARACTERS AS CREOLIZED TEXTS, PRAXEMES AND PRECEDENT PHENOMENA IN THE CONSCIOUSNESS OF YOUNG AUDIENCE WITH RESPECT TO POLITICAL ASSOCIATIONS - Ulianovskii, Andrei; Bryndina, Galina; Puiu, Yulia; Glinternik, Eleonora; Glinternik, Konstantin (Revista Inclusiones, 2019)
The work is devoted to the results of statistical processing of several hundreds of the most relevant characters and analyses thereof. The purpose of the study is to identify changes or shifts in understanding the world of youth and to establish their connection with the changes of the last 6–12 years that took place in the system of images that fill the Russian media space regarding the sphere of politics. An almost complete “reset” of the figurative system of youth has been recorded. The common international value-based agenda of the youth can be considered well-formed.